2016
DOI: 10.1146/annurev-cellbio-111315-125142
|View full text |Cite
|
Sign up to set email alerts
|

Cell Competition: Mechanisms and Physiological Roles

Abstract: Cell-competitive interactions are widespread in nature and determine the outcome of a vast variety of biological processes. A particular class of competitive interactions takes place when alterations in intrinsic cellular properties are sensed nonautonomously by comparison between neighboring cells, resulting in the selective elimination of one cell population. This type of cell competition was first described four decades ago in developing epithelia of Drosophila. In the last 15 years, further molecular and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 120 publications
0
117
0
Order By: Relevance
“…Cell competition is a conserved cell-elimination mechanism that functions through short-range cell-cell interactions whereby “winner” cells eliminate neighboring “loser” cells defective in some capacity, such as protein biogenesis, growth potential, or aberrant polarity (Amoyel and Bach, 2014; Baker, 2017; Claveria and Torres, 2016; de Beco et al, 2012; Maruyama and Fujita, 2017; Merino et al, 2016; Morata and Ballesteros-Arias, 2015; Tamori and Deng, 2011). Cell competition enables epithelia to actively eliminate emergent oncogenic cells as an endogenous tumor-suppression mechanism.…”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellsmentioning
confidence: 99%
“…Cell competition is a conserved cell-elimination mechanism that functions through short-range cell-cell interactions whereby “winner” cells eliminate neighboring “loser” cells defective in some capacity, such as protein biogenesis, growth potential, or aberrant polarity (Amoyel and Bach, 2014; Baker, 2017; Claveria and Torres, 2016; de Beco et al, 2012; Maruyama and Fujita, 2017; Merino et al, 2016; Morata and Ballesteros-Arias, 2015; Tamori and Deng, 2011). Cell competition enables epithelia to actively eliminate emergent oncogenic cells as an endogenous tumor-suppression mechanism.…”
Section: Cell Competition and The Active Extrusion Of Aberrant Cellsmentioning
confidence: 99%
“…Only a few studies reported cell competition phenomenon in mammals (28). Cells with a mutation in the Rpl24 gene (Rpl24 Bst/+ ), which encodes a component of ribosome protein in mouse, were outcompeted in chimeric embryos that were generated by injecting Rpl24…”
Section: Mdm4mentioning
confidence: 99%
“…Mutations in azot , a putative calcium binding protein gene induced by Myc cell competition, are reported to shorten lifespan and accumulate developmental defects, illustrating the possibility that cell competition optimizes progenitor cell pools during development and aging by eliminating defective cells [21*]. Cell competition phenomena in mammals seem to fit this paradigm [9]. It is suggested in the DNA damage field that ribosomal protein genes, being predominantly single copy and distributed throughout the genome in Drosophila as in mammals, might be ‘counted’ as sentinels of aneuploidy and other major genome alterations, and that Minute cells are eliminated due to their resemblance to aneuploid cells [48,49].…”
Section: What Is the Function Of Cell Competition?mentioning
confidence: 99%
“…In Drosophila , cell competition has only been observed in vivo in proliferating epithelial tissues, such as the undifferentiated imaginal discs that comprise the precursor cells for adult structures, in the ovarian follicle, and in the adult gut [1,7,8*]. Several examples of cell competition have now also been described in mammalian systems [9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation